2012
DOI: 10.1007/s00265-012-1329-0
|View full text |Cite
|
Sign up to set email alerts
|

Socially facilitated antipredator behavior by ringed salamanders (Ambystoma annulatum)

Abstract: Many aspects of animal behavior can be socially facilitated, including foraging behavior, exploration behavior, and antipredator behavior. Although larvae of the ringed salamander (Ambystoma annulatum) are not gregarious, they can live in high densities and face intense predation pressure during a short period following hatching. In a predator-recognition experiment, we found that these salamanders responded to chemical cues from dragonfly nymphs (Family: Libellulidae) with appropriate antipredator behavior (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…In a similar study, Crane et al. () demonstrated the social facilitation of antipredator behavior in another amphibian, the ringed salamander ( Ambystoma annulatum ). Given the recent advancements in our understanding of social learning in nonsocial species, we set out to determine whether amphibian larvae exhibit a second form of social learning.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In a similar study, Crane et al. () demonstrated the social facilitation of antipredator behavior in another amphibian, the ringed salamander ( Ambystoma annulatum ). Given the recent advancements in our understanding of social learning in nonsocial species, we set out to determine whether amphibian larvae exhibit a second form of social learning.…”
Section: Introductionmentioning
confidence: 80%
“…A recent study by Crane et al. () documented social facilitation of predator recognition by naïve ringed salamanders ( A. annulatum ). In this case, a larvae naïve to a predator is placed next to an experienced individual and simultaneously exposed to stimuli from that predator.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have documented a positive correlation between predation risk and prey activity level (Crane et al 2012;Casillas-Barrag an et al 2016), thus a decrease in activity level is one of the most common and effective behavioral anti-predator responses (DeSantis et al 2013). For example, larvae of the ringed salamander (Ambystoma annulatum) responded to chemical cues from dragonfly (Family: Libellulidae) nymphs with appropriate decreased activity in a predator-recognition experiment (Crane et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the tadpoles of B. gargarizans and D. melanostictus were fond of continuous swimming in their natural persistent pond habitats (personal observation); therefore, this may be a response to having enough benefit from swimming rather than a direct response to the predator. The continuous swimming of tadpoles of the family Bufonidae aids in their escape from G. affinis, and may be part of social facilitation of anti-predator behavior (Crane et al 2012). Previous research has shown that H. chinensis tadpoles are aggressive carnivores that often cannibalize larvae (Fan et al 2014), which may explain why this species can keep high survivorship in the presence of predators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation